Automated acute lymphoblastic leukaemia detection system using microscopic images. Issue 13 (11th October 2019) - Sukhia, Komal Nain; Ghafoor, Abdul; Riaz, Muhammad Mohsin; Iltaf, Naima
Abstract : An automatic and novel approach for acute lymphoblastic leukaemia classification is proposed. The proposed scheme is based on pre‐processing and segmentation of white blood cell nuclei using expectation maximisation algorithm, feature extraction, feature selection using principal component analysis and classification using sparse representation. The accuracy of the proposed scheme significantly outperforms the existing schemes in terms of acute lymphoblastic leukaemia classification.